Perspektif Guru dalam Penerapan Pembelajaran POE terhadap Kemampuan Analisis dan Keingintahuan Siswa SD pada Pembelajaran IPA di Kelas Tinggi - Wardani, Yusi Yustiani; Jayadinata, Asep Kurnia; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2021)
This research is motivated by science learning which emphasizes some analytical reasoning skills accompanied by an inculcation of character. This research aims to determine the teacher's perspective of POE learning implementation for students' analytical abilities and curiosity at the elementary school. This method used in this research is descriptive quantitative with survey design. The population in this research were elementary school teachers in Cileunyi district, Bandung. The number of samples is 56. The result show that POE learning (predict, observe, explain) implementation of science learning in high grades based on the teacher's perspective has a positive effect on students' analytical skills and curiosity significantly with a great category. This research has implications for improving the quality of good learning through POE learning as an alternative learning model that can improve students' analytical skills and curiosity in science learning.